2000
DOI: 10.1038/sj.ijo.0801291
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathology of prolactin secretion in obesity

Abstract: In many species prolactin is of biological importance and has a major role in determining the deposition and mobilization of fat. In human physiology, outside pregancy, prolactin secretion is altered by increasing body weight in both children and adults. Prolactin in this circumstance appears to be marker of hypothalamic ± pituitary function: the prolactin response to insulin-hypoglycaemia, thyrotrophin releasing hormone stimulation and other stimulatory factors may be diminished. In addition, obesity alters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 27 publications
(30 reference statements)
0
48
2
8
Order By: Relevance
“…Weight reduction, with accompanying decrease in insulin levels, has been shown to lead to a normalization of Prl response in most, but not all, circumstances [10]. In a study with obese subjects, no significant association was found between baseline Prl levels and the degree of obesity in these patients [23].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Weight reduction, with accompanying decrease in insulin levels, has been shown to lead to a normalization of Prl response in most, but not all, circumstances [10]. In a study with obese subjects, no significant association was found between baseline Prl levels and the degree of obesity in these patients [23].…”
Section: Discussionmentioning
confidence: 88%
“…In humans, outside pregnancy, Prl secretion is altered by increasing body weight in adults and children. However, no molecular basis has been found which links Prl with increasing body fat, weight and appetite, although some data suggest the involvement of Prl with leptin [10].…”
Section: Introductionmentioning
confidence: 99%
“…No correlation was observed between prolactin and BMI in our study; as previously mentioned study. It is suggested that obesity is occurs secondary to the changing in hypothalamic energy metabolism [13]. But, direct relationship between high prolactin and BMI is not clear [14].…”
Section: Discussionmentioning
confidence: 99%
“…When prolactin levels fall after treatment so does patients' weight (Greenman, Tordjman et al 1998). The relationship between prolactin level and weight could be due to the changes within central dopaminergic pathway and reduction in serotonin secretion (Kopelman 2000). Prolactin level has been found to be elevated in obese females (Kok, Roelfsema et al 2004) and levels falls after weight loss (Kok, Roelfsema et al 2006).…”
Section: Endocrine Disorders Causing Obesitymentioning
confidence: 99%
“…Prolactin level has been found to be elevated in obese females (Kok, Roelfsema et al 2004) and levels falls after weight loss (Kok, Roelfsema et al 2006). Raised prolactin level in obesity might be a result of hyperinsulinaemic state or alterations in doperminergic and serotoninergic activities centrally (Kopelman 2000). …”
Section: Endocrine Disorders Causing Obesitymentioning
confidence: 99%